PENGARUH PELATIHAN PENGEMBANGAN USAHA KULINER TERHADAP PERTUMBUHAN EKONOMI KREATIF - Fahrudin, Fahrudin; Sunarsih, Sunarsih; Ghufron, Moh. Idil (KEADABAN: Jurnal Sosial dan Humaniora, 2023)
Abstract: The term creative economy was first introduced by John Howkins in 2001. Starting in 1997, at that time John Howkins realized there was a change in the economic industry based on people's creativity. The creative economy in the digital era is currently growing, besides offering opportunities, it also creates competition. In Situbondo Regency, the culinary world and its actors receive special attention in facing competition. One of the steps taken by the Tourism, Youth and Sports Service is to hold culinary business development training. So the authors are interested in conducting this research which aims to find out how training in culinary development influences creative economic growth. This study uses quantitative methods with simple linear regression analysis. Data collection through observation, questionnaires and documentation. Questionnaires were distributed to 40 culinary business development training participants. Based on the results of the t test, the t count value is 2.209 > t table 2.024, so it can be concluded that culinary business development training has a positive effect on creative economic growth in Situbondo Regency. Meanwhile, based on the results of the R2  test analysis, it shows that the r square value is 0.486, which means that culinary business development training has an effect on creative economic growth of 48.6% and the remaining 51.4% is influenced by other variables outside of this study. Keywords: Training, Culinary Business Development, Creative Economy